Late Recurrence in Pediatric Cancer: A Report From the Childhood Cancer Survivor Study - Wasilewski-Masker, Karen (Oxford University Press, 2009)
BACKGROUND: An increasing percentage of childhood cancer patients are surviving their disease, but there is limited research on late recurrence. We sought to estimate late recurrence rates for the most common pediatric cancers and to determine risk factors for late recurrence. METHODS: The incidence of late recurrences, or first recurrences that occurred more than 5 years after diagnosis, was analyzed for the most common pediatric cancers using data from the Childhood Cancer Survivor Study, a retrospective cohort of 5-year survivors of childhood and adolescent cancers who were diagnosed between 1970 and 1986. A total of 12 795 survivors with no history of recurrence within 5 years after their original cancer diagnosis were included in the analysis, with a total of 217 127 person-years of follow-up. Cumulative incidence of late recurrence at 5, 10, 15, and 20 years after diagnosis was calculated using death as a competing risk. Adjusted relative rates of late recurrence were obtained using multivariable Poisson regression. All statistical tests were two-sided. RESULTS: Overall, 5-year survivors of pediatric cancers experienced a cumulative incidence of recurrent disease of 4.4%, 5.6%, and 6.2% at 10, 15, and 20 years, respectively. Cumulative incidence varied by diagnosis: Survivors of Ewing sarcoma and astrocytoma had the highest 20-year cumulative incidences at 13.0% (95% confidence interval [CI] = 9.4 to 16.5) and 14.4% (95% CI = 12.3 to 16.6), respectively. In multivariable analysis, the greatest risk factors for late recurrence included diagnosis, combination treatment with chemotherapy and radiation, earlier treatment era, and fewer years since diagnosis (P < .001 for all). CONCLUSION: Late recurrence is a risk for some pediatric cancers. By understanding diagnosis-specific risks, patients, families, and their medical providers can be better informed of the probability of cure.